2000
DOI: 10.1016/s1468-6996(01)00006-7
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of post-annealed SrTiO3 thin films prepared by mirror-confinement-type ECR plasma sputtering

Abstract: SrTiO 3 ®lms were synthesized on Pt/Ti/SiO 2 /Si multilayer substrates by mirror-con®nement-type ECR plasma sputtering without substrate heating. All ®lms were found to be well crystallized at a substrate temperature below 450 K. A low temperature post-annealing of the ®lms by electromagnetic-wave radiation drastically improved the crystallographic and electric properties of Pt/SrTiO 3 /Pt/Ti/SiO 2 /Si capacitors. The crystallinity of the ®lms indicated little variation by post-annealing, but irradiation of el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…The origin of this shift is considered to be associated with oxygen vacancies, which are positively charged. It is reported (ref a and references therein) that the existence of excess Sr at a condition of Sr/Ti > 1 and excess Ti at Sr/Ti < 1 induces the oxygen vacancy with two compensation electrons (V ·· O ) from the viewpoint of defect chemistry, expressed by the Kröger−Vink notation: For our as-deposited films (AHFT/SN was 1/1), the XPS result of Sr/Ti was 1.0/1.07 for a measured sample, showing that the film is nonstoichiometric at least in the measured surface layer of the film according to XPS analysis limit in depth (< 2 nm). The defect reactions mentioned above may bring about oxygen vacancies, which might act as electron donors and cause poor electrical properties.…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…The origin of this shift is considered to be associated with oxygen vacancies, which are positively charged. It is reported (ref a and references therein) that the existence of excess Sr at a condition of Sr/Ti > 1 and excess Ti at Sr/Ti < 1 induces the oxygen vacancy with two compensation electrons (V ·· O ) from the viewpoint of defect chemistry, expressed by the Kröger−Vink notation: For our as-deposited films (AHFT/SN was 1/1), the XPS result of Sr/Ti was 1.0/1.07 for a measured sample, showing that the film is nonstoichiometric at least in the measured surface layer of the film according to XPS analysis limit in depth (< 2 nm). The defect reactions mentioned above may bring about oxygen vacancies, which might act as electron donors and cause poor electrical properties.…”
Section: Resultsmentioning
confidence: 70%
“…Perovskite-type materials of ABO 3 , such as strontium titanate, barium titanate, and barium strontium titanate, are used in modern electronic devices. The SrTiO 3 (STO) thin film is a candidate dielectric material for capacitors in the next-generation dynamic random access memory (DRAM) with 1-Gbit density or higher, as well as in monolithic microwave integrated circuits (MMICs) because of its high dielectric constant (approximately 300) . It is also a candidate high-k dielectric to replace SiO 2 as a gate oxide film of MOSFETs …”
Section: Introductionmentioning
confidence: 99%
“…Besides, an increase in the heat treatment temperature from 500 to 750°C leads to a change in their thickness and a decrease in the forbidden band width E g . It is well known that the value of E g for direct optical transitions varies from 3.43 to 3.62 eV in SrTiO 3 crystalline films [18] and from 3.68 to 3.94 eV in amorphocrystaline structures [19]; in amorphous films, it increases to 4.07 eV [20].…”
Section: Introductionmentioning
confidence: 99%
“…However, to obtain a crystallized PZT film with good electrical properties, the process temperature could be higher than 500 'C because poor crystallinity of ferroelectric phase occurs and nonferroelectric second phase such as pyrochlore is metastable below 500 'C [2]. So far, there are a lot of investigations to lower the crystallization temperature by introducing seed layers [3][4][5][6][7][8][9][10][11][12][13][14]. Shimizu et al [3,14] reported that lead titanate is a good seed for polycrystalline PZT thin film deposition at 390 °C.…”
Section: Introductionmentioning
confidence: 99%